2019
DOI: 10.3390/nu11112694
|View full text |Cite
|
Sign up to set email alerts
|

Baicalein as a Potential Inhibitor against BACE1 and AChE: Mechanistic Comprehension through In Vitro and Computational Approaches

Abstract: One of the major neurodegenerative features of Alzheimer’s disease (AD) is the presence of neurotoxic amyloid plaques composed of amyloid beta peptide (Aβ). β-Secretase (BACE1) and acetylcholinesterase (AChE), which promote Aβ fibril formation, have become attractive therapeutic targets for AD. P-glycoprotein (P-gp), the major efflux pump of the blood-brain barrier (BBB), plays a critical role in limiting therapeutic molecules. In pursuit of discovering a natural anti-AD candidate, the bioactivity, physicochem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 37 publications
1
32
0
Order By: Relevance
“…During the last few years, flavonoids, including flavones, have attracted much interest because of their diverse bioactivities [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. Recent studies have indicated the abilities of flavones in inhibiting many enzymes [ 25 , 26 , 27 , 28 , 29 ], especially AChE [ 30 ] and BACE-1 [ 31 , 32 ]. Studies on the bioactivity of flavone derivatives against AChE and BACE-1 are thus promising for the discovery of novel therapeutic agents for AD.…”
Section: Introductionmentioning
confidence: 99%
“…During the last few years, flavonoids, including flavones, have attracted much interest because of their diverse bioactivities [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. Recent studies have indicated the abilities of flavones in inhibiting many enzymes [ 25 , 26 , 27 , 28 , 29 ], especially AChE [ 30 ] and BACE-1 [ 31 , 32 ]. Studies on the bioactivity of flavone derivatives against AChE and BACE-1 are thus promising for the discovery of novel therapeutic agents for AD.…”
Section: Introductionmentioning
confidence: 99%
“…As per the results obtained from the in-vitro and in-silico findings, baicalein demonstrates the properties of a non-competitive inhibitor. Allosteric modulation has been previously reported for baicalein [31]. Non-competitive inhibition underlines the possibility of the inhibitor molecule binding to either the enzyme alone or the enzyme-substrate complex.…”
Section: Discussionmentioning
confidence: 75%
“…Finally, we investigated whether the MGO platform can be used for the detection of β-secretase, which is considered to be an important Alzheimer’s disease marker [ 42 , 43 ]. The MGO FRET biosensors were incorporated with the β-secretase-specific peptide (EVNLDA) [ 44 ]. Fluorescence recovery was achieved by the cleavage of the peptide between Leu and Asp by β-secretase, resulting in the release of FITC-EVNL.…”
Section: Resultsmentioning
confidence: 99%